The Four-line Algorithm for the Treatment of Unilateral Cleft Lip - Franklin J. Paredes, MD; Edwar C. Alvarez, MD; Emily M. Jones, BS; Valeri K. Paredes, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Several factors affect the outcome of a repaired unilateral cleft lip (UCL). Some of these, like the surgeon’s expertise, are hard to evaluate, whereas others can be better evaluated objectively using the cleft severity index and the surgical technique used. Methods:. This study includes patients of Operation Smile Ecuador and was done in 2 parts. The retrospective part uses the medical records of 298 patients with UCL treated by Operation Smile Ecuador from January 2015 to December 2017. The correlation of the photographed measurements, surgical technique, and evolution of the patients was studied. In the prospective part, the participant surgeons of this article applied the algorithm to 136 patients treated from January 2018 to December 2019. Results:. In the retrospective study, the resulting symmetry varied significantly among most Unilateral Cleft Asymmetry Index presurgical classifications, and 34% of the results were deficient. The four-line algorithm was developed using the case-technique analysis of the retroactive study. The algorithm was applied in the prospective part, which resulted in no deficient cases and 81% optimal results. There were significantly better results after applying the four-line algorithm for patients classified as Unilateral Cleft Asymmetry Index degrees III and IV (P < 0.001 and P = 0.041, respectively). Conclusions:. Even though the cleft severity in the UCL is an important prognostic factor, the results of this study show that there are no universal surgical techniques to achieve optimal results. The four-line algorithm proposes to use a case-specific surgical technique to achieve the best functional and aesthetic result for our patients.